Developing English teaching and learning materials for nursing students of Universitas ‘Aisyiyah Yogyakarta - Annisa Nurul Ilmi; Suwarsih Madya (LingTera, 2019)
The aim of this research and development study was to develop a set of English teaching and learning materials for nursing students. The development of the materials was carried out in three phases: planning, developing, and evaluating. The research findings revealed the nursing students’ needs concerning media, language instruction, assignments, lecturer’s and student’s roles,  setting of the class, learning activities, use of English for the students, students’ intention to learn English, setting in which English was used, learning themes, input texts, students’ English proficiency, target culture knowledge, appropriateness of the English book used, English skills the students want to improve, and layout of the materials. The means of materials were 3.95 in terms of the language teaching and 3.63 in terms of the content. The means of three units were 3.43, 3.44, and 3.33. The means implied that the developed materials were appropriate to be used in the teaching and learning process as the materials met the nursing students’ needs and interest.